Training on making composter bins for household organic waste treatment - Yunita Ismail Masjud; Filson Maratur Sidjabat; Filda Rahmiati; Grace Amin (University of Merdeka Malang, 2022)
Waste management in households can make waste as a resource and provide benefits for the manager. One way to manage organic waste is to make it into liquid fertilizer using composting bins that can be used independently by households. In this community service activity aims to educate households on how to use composting barrels. The activities carried out are by holding training on making barrels as well as procedures for turning organic waste into liquid pupu for housewives who directly handle waste in their households. This activity was carried out in a residential area in Cikarang, Bekasi Regency with a total of 45 participants. The training was conducted for one day, starting with a briefing on the formation of a RW-level waste management organization, followed by making composting bins and making bins together. Participants in this training are generally 40-45 years old (40%) with high school education (64%). In this training, 1 composting bin has been successfully made using a container that was used as a chemical container that was deliberately purchased from a secondhand goods trader. This training is expected to educate housewives to be able to manage organic waste into liquid fertilizer and can increase their income because it still has economic value.